Estimating suitable starch extraction from mango seeds using analytical hierarchy process (AHP) method - Ahmad Shahrim, Nur’Aishah Ahmad; Sarifuddin, Norshahida; Mohd Zaki, Hafizah Hanim; Ahmad Azhar, Ahmad Zahirani (Trans Tech Publications Ltd, 2020)
The mango seed was extracted to starch via distillation, alkaline, sedimentation and centrifugation methods. Based on the analysis, different starch extraction methods resulted in different proximate composition, physicochemical, morphological, structural, functional and thermal properties of starch. As such, it is necessary to choose a suitable starch extraction method to fabricate starch-based film for packaging application. Therefore, in this study, Analytic Hierarchy Process (AHP) method was applied for performing the decision-making process. Based on the AHP method, it was found that, the best alternative for starch-based films is distillation method.